IXGAMES – Implementing Internet exchange point, exclusively for games - Sousa, Alexandre J. Barbieri de (2008)
An ever-growing number of games is available on the market and more and more features are incorporated each day. The increase in the player base and game enhancements demand that games work on a network with reliable speed and efficient time response. This article proposes a high speed network infra-structure exclusive for games,. This network, called IXGAMES originated from experiments with shared routing through Internet Exchange Point (IXP). IXGAMES opens new business opportunities for operators/ Providers and game companies that, not only will provide financial return, but will also allow them to offer better quality service to their customers